The Effect of Training and Work Discipline on Employee Productivity at PT Anugerah Agung in Jakarta - Yan Kristian Halomoan (Jurnal Ad'ministrare, 2020)
Employee work productivity is a very important factor in supporting a company's business success. This study aims to determine the effect of training and Work discipline on employee productivity at PT. Anugerah Agung in Jakarta. The method used was explanatory research with a sample of 82 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study training significantly influence employee productivity by 34.0%, hypothesis testing obtained significance 0,000 <0.05. Work Discipline has a significant effect on employee productivity of 42.6%, hypothesis testing obtained significance of 0,000 <0.05. Work training and discipline simultaneously have a significant effect on employee productivity by 50.5%, hypothesis testing obtained significance 0,000 <0.05.